Modeling the impact of the difference in cross-protection data between a human papillomavirus (HPV)-16/18 AS04-adjuvanted vaccine and a human papillomavirus (HPV)-6/11/16/18 vaccine in Canada - Kohli Michele; Lawrence Donna; Haig Jennifer; Anonychuk Andrea; Demarteau Nadia (BMC, 2012)
Background In Canada, two vaccines that have demonstrated high efficacy against infection with human papillomavirus (HPV) types −16 and −18 are available. The HPV-6/11/16/18 vaccine provides protection against genital warts (GW) while the HPV-16/18 vaccine may provide better protection against other oncogenic HPV types. In this analysis, the estimated clinical and economic benefit of each of these vaccines was compared in the Canadian setting. Methods A Markov model of the natural history of HPV infection among women, cervical cancer (CC) and GW was used to estimate the impact of vaccinating a cohort of 100,000 12-year-old females on lifetime outcomes and healthcare system costs (no indirect benefit in males included). A budget impact model was used to estimate the impact of each vaccine by province. Results In the base case, vaccination with the HPV-16/18 vaccine was predicted to prevent 48 additional CC cases, and 16 additional CC deaths, while vaccination with the HPV-6/11/16/18 vaccine was predicted to prevent 6,933 additional GW cases. Vaccination with the HPV-16/18 vaccine was estimated to save 1 additional discounted quality adjusted life year (QALY) at an overall lower lifetime cost to the healthcare system compared to the HPV-6/11/16/18 vaccine (assuming vaccine price parity). In sensitivity analyses, the HPV-6/11/16/18 vaccine was associated with greater QALYs saved when the cross-protection efficacy of the HPV-16/18 vaccine was reduced, or the burden of GW due to HPV-6/11 was increased. In most scenarios with price parity, the lifetime healthcare cost of the strategy with the HPV-16/18 vaccine was predicted to be lower than the HPV-6/11/16/18 vaccine. In the probabilistic sensitivity analyses, the HPV-16/18 vaccine provided more QALY benefit than the HPV-6/11/16/18 vaccine in 49.2% of scenarios, with lower relative lifetime costs in 83.5% of scenarios. Conclusions Overall, the predicted lifetime healthcare costs and QALYs saved by implementing each of the vaccines are similar. Vaccination with the HPV-16/18 vaccine is expected to be associated with reduced CC disease morbidity and mortality compared to vaccination with the HPV-6/11/16/18 vaccine. Differences in these outcomes depend on the extent of cervical disease prevented by cross-protection and the burden of GW caused by HPV-6/11.